Nominalization in Priyanka Chopra’s Selected Speeches - Sonia Margareta Pasaribu; Eddy Setia; Dian Marisha Putri (Talenta Publisher, 2022)
This study aims to find out types of nominalization used in Priyanka Chopra’s selected speeches and the realizations. The selected speeches were taken from written sources and videos on the internet consisting of three speeches. This research used a descriptive qualitative method by applying theory of nominalization in Systemic Functional Linguistics by Quirk et al. The data collection techniques were conducted by applying a documentation method. The documents used to support this study were in the form of videos and transcriptions of the speeches on the internet. The results showed that not all the three types of nominalization were used in the three selected speeches. The nominalization with the gerundive noun type was used in all the three selected speeches. There were 6 gerundive nouns (14.6%) in the first speech, 7 gerundive nouns (25%) in the second speech, and 4 gerundive nouns (21%) in the third speech. The nominalization with verbal noun type was only used 1 (2.4%) among the three selected speeches which was in the first speech. Meanwhile, the deverbal noun type was used most in all the three selected speeches. There were 34 deverbal nouns (83%) in the first speech, 21 deverbal nouns (75%) in the second speech, and 15 deverbal nouns (79%) in the third speech. The nominalizations were realized by suffixations and conversions. The nominalizations were formed in the presence of the suffixes –dom, -er, –ing, -ion, -ity, -ment, and -or. Also, they were formed by conversion, such as the nouns care, cause, experience, and waste.